Improving Student-Based Feedback Mechanism for Learning Improvement in Economic Development Study Program at State University of Makassar - Muh Fardan Ngoyo; Sri Astuty; Dirmansyah Darwin; Adi Zulkarnaen; Hafid Sumarwadji (Jurnal Pengabdian Masyarakat Bangsa, 2026)
Student feedback is essential for improving teaching quality; however, conventional course evaluations often provide limited insights into students' learning experiences. This community engagement initiative developed and implemented the  Student Perspective Evaluation and Academic Feedback (SPEAK) system in the Economic Development Study Program at the State University of Makassar from May to Juni 2025. Using a participatory approach, the program involved needs assessment, digital instrument development, training, simulation, and dissemination. The implementation involved 25 student participants, of whom 23 (92%) demonstrated the ability to independently use the digital SPEAK instrument following the training and simulation. The system integrated quantitative ratings with qualitative reflections, enabling lecturers to obtain more actionable feedback on students’ learning experiences and teaching practices. These results indicate that SPEAK provides a feasible and participatory mechanism for strengthening evidence-based reflection and supporting learning improvement and contributes to SDG 4 (Quality Education) through enhanced teaching and learning quality.